Nursing performance in the craniotomy perioperative period: A review (Research, Society and Development, 2024)
The objective of this study was to analyze nursing assessment and performance regarding patient positioning in the perioperative period of posterior fossa craniotomy. To carry out this article, an integrative literature review was used, in accordance with the bases of the Virtual Health Library. The object of study and the key words were: “surgical positioning” and “nursing”. As inclusion criteria, the following filters were assigned: full text, published in Portuguese, published in English and in the form of an article. The exclusion criteria were considered: articles that do not allow downloading, duplicate articles and those that are not related to the object of study, totaling 6 articles. It was found that minimizing direct or indirect damage to the patient, inhibiting injuries and complications that would lead to sequelae and mortality. Teamwork is an important strategy, preserving patient safety and integrity throughout the perioperative process. Nursing work with instruments, protocols, continuing and permanent education of the team, is essential so that the assessment of iatrogenesis and risk in the development of injuries resulting from surgical positioning, anatomical and physiological changes in the patient, carried out correctly, avoids their worsening or complication, as in a cardiorespiratory arrest, with a team unprepared to carry out the maneuver and interventions.